A Comprehensive Review of Vitamin C in Autoimmune Skin Disease Management: Tinjauan Komprehensif tentang Vitamin C dalam Manajemen Penyakit Kulit Autoimun - Eltayef, Emad M .; Nasif, Zaizafoon N. (Academia Open, 2025)
General Background: Autoimmune skin diseases significantly impact patients’ quality of life and, in severe cases, contribute to increased morbidity and mortality. While these diseases remain incurable, management strategies improve patient outcomes. Specific Background: Vitamin C (ascorbic acid), a key antioxidant, has been recognized for its role in disease management, yet its effectiveness compared to other supplements, such as vitamins D and E, remains underexplored. Knowledge Gap: Previous studies have not comprehensively evaluated the potential of vitamin C in autoimmune skin disease management, particularly in varying delivery methods and dosage effects. Aims: This review systematically examines the role of vitamin C in treating autoimmune skin diseases, synthesizing data from peer-reviewed studies, systematic reviews, and authoritative reports. Results: Vitamin C modulates innate and adaptive immunity, enhances collagen synthesis, supports skin wound healing, and regulates inflammatory processes. However, its instability and low bioavailability pose challenges that require targeted drug delivery strategies. Novelty: Unlike prior research, this review consolidates evidence on the therapeutic potential of vitamin C, addressing its limitations and proposing integrative approaches. Implications: Findings highlight the need for optimized delivery methods and further research into vitamin C’s role in autoimmune disorders, offering a potential alternative strategy for improving disease management. Higlights: Autoimmune skin diseases affect quality of life and lack cures. Review vitamin C’s role in managing autoimmune skin diseases. Vitamin C aids immunity and healing but requires optimized delivery methods. Keywords: Vitamin C, ascorbic acid, systemic lupus erythematosus, psoriasis, autoimmune skin disease, pemphigus, scleroderma, dermatomyositis, vasculitis, and vitiligo.